Regulatory interaction between metabolite transporters coordinates glucose and exometabolite fluxes to drive bioenergetics - Noa Yehoshua; Ahlam Khamaysi; Liana Shimshilashvili; Aharon Keshet; Mahmoud Taha; Moran Fremder; Hadar Eini-Rider; Ehud Ohana (Nature Communications)
Abstract The composition of tricarboxylic acid cycle metabolites in the external environment of cells determines vital physiological functions, including nutrient and mineral absorption, inflammation, and cellular energy management. Here, we study how the transport of external metabolites into the cells functions as an independent metabolic pathway that controls cellular energy. We show that liver cells orchestrate simultaneous fluxes of glucose and the omnipotent metabolite citrate across the cell membrane, acting as a first line metabolic pathway that responds to nutrient availability. Using functional mapping and gene silencing, we delineate the underlying molecular mechanism showing that the liver citrate transporter (NaCT) interacts with glucose transporters (Glut) and the anion transporters. The interaction is mediated by a specific region of the NaCT protein to reciprocally regulate the transport functions. Our findings describe an independent mechanism that coordinates external metabolites and glucose balance, thus driving key energy management processes in response to nutrient availability in the liver.